Filosofando en medio del caos : Agustín de Hipona y sus enseñanzas sobre la verdad y la justicia - Velázquez, Hugo José Francisco (Sapientia, 2015)
This article refers to one of the most important medieval philosophers of the western thinking, Augustine of Hippo. In this paper I will try to examine and to analyze, first, the biographical, social and political context of his epoch, since we cannot understand the thought of a philosopher out of the circumstances in which his philosophy was created; after analyzing the historical context I will try to justify the position that holds that saint Augustine was really a medieval thinker, in spite of the fact that he is not located inside the temporary limits that the tradition indicates for the Middle Age. Secondly, I will try to reveal his lessons of truth and justice; and, finally, I will try to locate them inside of the qualifying schemes of Jorge Saltor and Nicasio Barrera.